Quản lí chất lượng chương trình đào tạo ngành Công nghệ thông tin ở các trường đại học theo hướng tiếp cận mô hình quản lí chất lượng tổng thể: Một nghiên cứu tổng quan - Đặng Văn Em, Đặng Văn Em; Nguyễn Thị Hảo, Nguyễn Thị Hảo (Tạp chí Giáo dục, 2026)
In the context of digital transformation, research on the application of Total Quality Management (TQM) in higher education has been widely conducted; however, at the level of Information Technology academic programs, specialized theoretical frameworks remain limited. This article systematizes the theoretical foundations of program quality management based on the TQM model, thereby offering several observations and proposing initial, direction-oriented recommendations for the application of TQM in managing Information Technology training programs at higher education institutions. The findings provide a theoretical basis for practical implementation and help orient future empirical research in Vietnam.